1987
DOI: 10.1016/0014-5793(87)80963-8
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of two 67 kDa calcium‐binding proteins from pig lung differing in affinity for phospholipids and in anti‐phospholipase A2 activity

Abstract: Two 67 kDa proteins adsorbed to membranes in the presence of Ca 2t have been purified to homogeneity from pig lung using conventional procedures, followed by calcium-dependent affinity chromatography on polyacrylamide-immobilized phosphatidylserine. The two proteins were, respectively, excluded (67E) and retained (67R) on the column in the presence of Ca 2f . On the basis of amino acid composition and isoelectric point, 67R was identified as 67 kDa calelectrin/calcimedin, whereas 67E could be differentiated fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

1988
1988
1992
1992

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 37 publications
2
17
0
Order By: Relevance
“…Interestingly, the extracellular compartment of the sponge also contains the inhibitor of phospholipase API calelectrin (Fauvel et al, 1987). We found that this protein is associated with the sponge AF particle and noncompetitively inhibits the homologous enzyme.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Interestingly, the extracellular compartment of the sponge also contains the inhibitor of phospholipase API calelectrin (Fauvel et al, 1987). We found that this protein is associated with the sponge AF particle and noncompetitively inhibits the homologous enzyme.…”
Section: Discussionmentioning
confidence: 81%
“…In view of an earlier finding that phospholipase A2 activity is inhibited by calelectrin (Fauvel et al, 1987), we preincubated both the cell extract and the extracellular material with antibodies against calelectrin prior to the determination of enzyme activity. After this treatment, the activity increased 3.4-fold in the extracellular material, but only 1.15fold in the cellular extract (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Beside anticoagulant activity, Annexin Vr and Annexin VIIIr were found to inhibit the activity of soluble pancreatic phospholipase A2, when (3H)-oleic acid labeled E. coli membranes are used as substrate [10]. Using comparable in vitro systems other members of the annexin family were found to inhibit the activity of soluble or solubilized phospholipases [18][19][20]. In the isolated lung human recombinant lipocortin I (Annexin I) was able to suppress thromboxane synthesis, when added to the perfusion medium [21].…”
Section: Discussionmentioning
confidence: 99%
“…This model has been found useful for studies employing soluble or solubilized phospholipases. As stated above, conclusions concerning the phospholipase inhibitory effect and mechanism of action of annexins are primarily based on studies using soluble pancreatic phospholipase A2 as model enzyme and artificial membranes as substrate [10,[18][19][20]. The availability of large amounts of recombinant Annexin V enabled us to study the effect of annexins on PL hydrolysis in a more natural setting, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Basic FGF was purified from bovine brain as in [11,12]. Lipocortin from pig lung was prepared as in [13] and kindly provided by Drs Josette Fauvel and Hugues Chap 0d 101 INSERM, Toulouse).…”
Section: Methodsmentioning
confidence: 99%